2012
DOI: 10.12674/ptk.2012.19.2.039
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Ability to Balance Posture and Proprioception by Horse Riding Simulator and Galvanic Vestibular Stimulation

Abstract: The purpose of this study is to examine the influence of a horse riding simulator and galvanic vestibular stimulation on improving the ability to balance posture and proprioception. Thirty healthy adults participated and were randomly assigned to a horse riding simulator group (n1=10), galvanic vestibular stimulation (GVS) group (n2=10), control group (n3=10). Experiment groups were trained 3 times per week over 6 weeks. The ability to balance posture was measured by force plate and proprioception was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
(2 reference statements)
0
7
0
2
Order By: Relevance
“…Lee and Jeong13 ) reported that horseback simulator exercise increased muscle strengths in the femoral and the lumbar areas of 20 normal female students. Cho et al14 ) noted that horseback riding simulator exercise was effective at improving postural balance ability and proprioceptive sense in a study of 30 normal adults. Kuczyński and Słonka15 ) conducted horseback riding simulator exercise for 25 cerebral palsy children for 12 weeks, and observed a significant improvement in their left and right balance ability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee and Jeong13 ) reported that horseback simulator exercise increased muscle strengths in the femoral and the lumbar areas of 20 normal female students. Cho et al14 ) noted that horseback riding simulator exercise was effective at improving postural balance ability and proprioceptive sense in a study of 30 normal adults. Kuczyński and Słonka15 ) conducted horseback riding simulator exercise for 25 cerebral palsy children for 12 weeks, and observed a significant improvement in their left and right balance ability.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Beinotti et al17 ) conducted horseback riding exercise for 20 stroke patients and observed enhancement of their gait and balance abilities. Cho et al14 ) reported that horseback riding simulator exercises were effective at improving postural balance ability and proprioceptive sense, while Nashner and Peter18 ) reported that proprioceptive sense–improving exercises elicited a larger improvement in postural sway when the eyes were closed. In the present study, ECB showed significant differences between the groups after the intervention, indicating HEG's proprioceptive senses improved more than MEG's proprioceptive senses; whereas, EOB did not show a significant difference.…”
Section: Discussionmentioning
confidence: 99%
“…Lee and Jeong 13) reported that horseback simulator exercise increased muscle strengths in the femoral and the lumbar areas of 20 normal female students. Cho et al 14) noted that horseback riding simulator exercise was effective at improving postural balance ability and proprioceptive sense in a study of 30 normal adults. Kuczyński and Słonka 15) conducted horseback riding simulator exercise for 25 cerebral palsy children for 12 weeks, and observed a significant improvement in their left and right balance ability.…”
Section: Discussionmentioning
confidence: 99%
“…The horseback riding simulator exercise also improved the thigh and lumbar muscular strengths of 20 normal female adults8 ) , and was effective at improving the balance ability and proprioceptive senses based on the results of 30 normal adults9 ) . Kang et al10 ) demonstrated significantly increased basal fitness, flexibility, and muscular function of 20 normal adults who used indoor horseback riding exercise equipment for 4 weeks.…”
Section: Discussionmentioning
confidence: 99%